Large-deflection and postbuckling of beam-columns with non-linear semi-rigid connections including shear and axial effects. (December 2015) - Giraldo-Londoño, Oliver; Monsalve-Giraldo, J. Sebastian; Aristizabal-Ochoa, J. Dario
Abstract: The non-linear large deflection-small strain analysis and post-buckling behavior of an out-of-plumb Timoshenko beam-column of symmetrical cross section subjected to end loads (forces and moments) with non-linear bending connections at both ends, and its top end partially restrained against transverse and longitudinal translations are developed in a classical manner. A set of non-linear equations based on the "modified shear equation" that includes the effects of (1) shear deformation and the shear component of the applied axial forces; and (2) shortening of the beam-column due to both axial forces and "bowing" are presented. The proposed method and corresponding equations can be used in the large deflection-small strain analysis of Timoshenko beam-columns with non-linear bending connections, as well as lateral and longitudinal non-linear restraints at the top end. This paper is an extension of previous work presented by the senior author on the large deflection and post-buckling behavior of Timoshenko beam-columns with linear elastic semi-rigid connections and linear elastic lateral bracing. Three comprehensive examples are included that show the effectiveness of the proposed method and corresponding equations. Results obtained in the three examples are verified against analytical solutions available in the technical literature and against results from models using the FEM program ABAQUS. Highlights: The large deflection-small strain and post-buckling analyses of Timoshenko beam-columns are studied. Shear deformations and column shortening due to "bowing" are implemented using the Haringx approach. The beam-column is partially restrained by non-linear transverse, axial and rotational springs. The results correlate very well with other theoretical solutions and ABAQUS.